Milan system in salivary gland lesions: Its diagnostic and clinical relevance - Singh, Smriti; Parveen Rana; Kaur, Swaran; Garg, Uma; Agarwal, Deepti; Saini, Abhishek (Asian Journal of Medical Sciences, 2021)
Background: The salivary gland lesions constitute around 3–6% of all head-and-neck lesions and have always posed a diagnostic riddle for the cytopathologists around the world. Since the majority of these lesions need surgical excision, it is, therefore, important to diagnose these lesions with utmost precision to prevent over or under stage procedures. The recent adaption of Milan system of reporting aims to establish a uniform, accurate, and consensual reporting system which bridges the communication between the pathologists and the clinicians. Aims and Objectives: The current study aims to assess the diagnostic application of Milan system and aims to reclassify the lesions according to it. Materials and Methods: The current study was conducted at our institute during 1 year period. All salivary gland swellings presenting to the fine-needle aspiration cytology (FNAC) section during this period were included in the study. Along with this, records and slides of cases of salivary gland lesions were retrospectively assessed. All relevant data and radiologic findings were retrieved from the case records. FNAC was done using 23 G needle. The slides were stained with both Leishman and Papanicolaou stain wherever possible. Quantitative data were expressed as mean and standard deviation and percentages. All the 83 lesions were reclassified as per the Milan system. Histopathology was available in 42 cases. Inclusion criteria: All the samples of the patient having salivary gland lesion(s) whose FNAC were performed in the department of pathology. Statistical Analysis: Data were be entered into Microsoft Excel spreadsheets. For quantitative data, mean and standard deviation were calculated. For qualitative data, percentage and proportion were calculated. Sensitivity, specificity, and spearman correlation between FNAC and histopathology were calculated. P<0.05 was considered statistically significant. Results: The total of 83 cases was included in our study. The cytological analysis was done and all cases were classified as per Milan system. The age of patients ranged from 4 years to 77 years with a mean age of 43 years. Parotid was the most frequently involved gland in which a total of 51 cases (61.4%) were reported. The most common benign tumor reported on cytology was pleomorphic adenoma and the most common malignant tumor reported was adenoid cystic carcinoma. On recategorization of lesions as per Milan system, the category IVA, that is, benign salivary gland neoplasm had the maximum number of lesions (40) accounting for 48.1% of all the lesions. Histopathology was available in 42 cases. The predominant lesion on histopathology was pleomorphic adenoma (22). On statistical analysis of the data, the sensitivity was 71.4%, specificity was 96.1%, diagnostic accuracy as 62.1%, and positive and negative predictive value as 83.3 and 92.5%, respectively. Conclusion: Risk stratification approach in classifying salivary gland cytology aspirate as per Milan system provides a standardized reporting and better communication to clinician.